Incidental Detection of a Hodgkin Lymphoma on 18F-Choline PET/CT and Comparison With 18F-FDG in a Patient With Prostate Cancer. (August 2015) - Goineau, Aurore; Colombié, Mathilde; Rousseau, Caroline; Sadot-Lebouvier, Sophie; Supiot, Stéphane
Abstract : Abstract: Combined PET/CT scanning with 18 F-FDG is in current use in Hodgkin lymphoma. New tracers have been developed, such as 18 F-choline in prostate cancer. Its use is under investigation in other solid tumors (eg, brain, liver, lung). We report a case of Hodgkin lymphoma incidentally detected on 18 F-choline PET/CT in a prostate cancer patient and show a comparison with 18 F-FDG PET/CT. 18 F-choline PET/CT detected more lymph node lesions than the 18 F-FDG PET/CT for this patient. Comparative studies of the 2 tracers might help fine-tune treatments and, in particular, delineate target zones in radiation therapy.